Start with Why: How Great Leaders Inspire Everyone to Take Action - Kudaibergenova, R.S.; Koigeldiyeva, A.A. (KAZGUU Liberal Arts Digest Volume 3. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
The name of the book is Start with Why: How Great Leaders Inspire Everyone to Take Action. The author is Simon Sinek who is considered an American-British writer and inspiring speaker. His aim in writing the book is to help people accomplish the job that inspires them, and then use real-life examples of exceptional leaders to demonstrate how they communicate and how you may apply their ideas to inspire others. Sinek (2009) found that his major purpose is to teach people how leaders may motivate each other and what questions they should ask before taking any action. He highlights three major questions that are relevant to everyone. He ignores ancillary topics and just covers solutions that truly work in this book. In addition, he shows why it is critical to begin your business by asking the appropriate questions.
Keywords: golden circle, WHY strategy, action theories, behaviour